2019
DOI: 10.3390/f10080651
|View full text |Cite
|
Sign up to set email alerts
|

Norway Spruce (Picea abies L.) Provenances Use Different Physiological Strategies to Cope with Water Deficit

Abstract: Research Highlights: In this study, we found different regulatory mechanisms in two contrasting provenances of Norway spruce responding to progressive drought stress. Background and Objectives: In the context of climate and environmental changes, the following question of high importance in scientific studies is: How will Norway spruce, which forms a dominant component in European mountain and boreal forests, be able to cope with the increasing frequencies and intensities of drought periods? The aim of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…The fir provenances originating from relatively high altitudes (from wetter and colder localities) achieved and maintained relatively high efficiency of PSII photochemistry, even more they enhanced their efficiency at PSII level after mild water stress. These findings concur with those from provenances of other species, i.e., Fagus sylvatica (Kučerová et al 2018, Quercus suber L. (Aranda et al 2005), Picea abies (Oleksyn et al 1998, Jamnická et al 2019, and also Abies alba (Peguero-Pina et al 2007, reflecting the variation in the adaptation and acclimation abilities of forest tree species under conditions of a changing climate with possible use for forestry purposes.…”
Section: Discussionsupporting
confidence: 81%
“…The fir provenances originating from relatively high altitudes (from wetter and colder localities) achieved and maintained relatively high efficiency of PSII photochemistry, even more they enhanced their efficiency at PSII level after mild water stress. These findings concur with those from provenances of other species, i.e., Fagus sylvatica (Kučerová et al 2018, Quercus suber L. (Aranda et al 2005), Picea abies (Oleksyn et al 1998, Jamnická et al 2019, and also Abies alba (Peguero-Pina et al 2007, reflecting the variation in the adaptation and acclimation abilities of forest tree species under conditions of a changing climate with possible use for forestry purposes.…”
Section: Discussionsupporting
confidence: 81%
“…This region harbors high genetic diversity due to multiple refugial areas and postglacial migration history (Tollefsrud et al, 2008 ; Mihai et al, 2020 ). Besides testing for immediate effects of extreme drought on radial growth, further studies on Norway spruce found significant provenance variation of the long-term growth reactions to climate parameters (i.e., Suvanto et al, 2016 ; Klisz et al, 2019 ) or different physiological strategies of seedlings to cope with water limitations (Jamnická et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This region harbors high genetic diversity due to multiple refugial areas and postglacial migration history (Tollefsrud et al, 2008;Mihai et al, 2020). Besides testing for immediate effects of extreme drought on radial growth, further studies on Norway spruce found significant provenance variation of the long-term growth reactions to climate parameters (i.e., Suvanto et al, 2016;Klisz et al, 2019) or different physiological strategies of seedlings to cope with water limitations (Jamnická et al, 2019). Evidence for genetic variation of climate-growth response within silver fir comes from dendroecological analysis throughout the Carpathian Mountains, demonstrating that radial growth within populations originating from Apennine origin, is more strongly driven by summer temperatures, whereas the increment of Balkan populations is more driven by summer drought (Bosela et al, 2016).…”
Section: Genetic Variation In Drought Response Among Provenancesmentioning
confidence: 99%
“…Despite the high biological importance for the Caatinga, little is known about the physiological responses of these species under water deficit, especially during the seedling phase the most vulnerable phase of the forest tree life (JAMNICKÁ et al, 2019). Due to its climatic and pedological characteristics, the semi-arid region where the Caatinga is inserted presents itself as extremely susceptible to the changes resulting from the climate changes expected as a result of global warming.…”
Section: P a G E | 59mentioning
confidence: 99%